LEGAL NATURE OF A SMART-CONTRACT AND ISSUES OF ITS APPLICATION IN THE FIELD OF DIGITAL ASSETS - К.Г. Некіт (Економіка та право, 2024)
The article looks into the concept and legal nature of smart contracts, as well as the issues that arise during the use of smart contracts in the field of digital assets. The technical and legal aspects of the concept of a smart contract are considered. Models of use of smart contracts are described. Scientific and legislative approaches to determining the legal nature of smart contracts are presented. The dual legal nature of a legal smart contract is analyzed: as a form of transaction and an object of copyright. Some issues in the field of protection of the rights of smart contract parties are considered. Based on the findings, temporary solutions in the field of using smart contracts are proposed.